DESIGNING SOCIAL MEDIA-BASED SCIENCE LEARNING MEDIA AS ALTERNATIVE MEDIA IN ELEMENTARY SCHOOLS - Tongam E Panggabean; Setiadi, Kusno; Aisyah Hanim, Siti (Adisam Publisher, 2024)
The process of learning activities currently follows technological developments, one of which is learning via the internet. One effort to overcome students' passive attitude is to increase students' involvement in learning through the use of learning media. There are many learning media that can be used in the learning process, especially in science subjects. This includes images, videos and animated media and can use existing school infrastructure to provide these media. One of them is the use of social media-based learning media. Instagram social media is very suitable as an online learning medium because Instagram is very easy to use and is an application that is familiar to the millennial generation. The use of Instagram as a learning medium has emerged as an alternative solution in improving the quality of learning in the current digital era. Instagram social media is very fast in conveying information and easy to access by students. Using Instagram as a learning medium can also increase student participation in learning activities. With more intense interaction and attractive visuals, students will be more motivated to learn.